2015
DOI: 10.1094/pdis-10-14-1060-re
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Phylogenetic Relationships of Plant-Parasitic Nematodes Associated with Turfgrasses in North Carolina and South Carolina, United States

Abstract: The near-full-length 18S ribosomal DNA (rDNA) gene and internal transcribed spacer 1 region were amplified and sequenced from 52 nematode populations belonging to 28 representative species in 13 families recovered from turfgrasses in North Carolina (38 populations) and South Carolina (14 populations). This study also included 13 nematode populations from eight other plant hosts from North Carolina for comparison. Nematodes were molecularly characterized and the phylogenetic relationships were explored based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 32 publications
4
72
0
5
Order By: Relevance
“…1. A lack of taxonomic resolution among criconematid genera was similarly noted by Zeng et al (2015) in their 18S rDNA phylogenetic analysis.…”
mentioning
confidence: 63%
“…1. A lack of taxonomic resolution among criconematid genera was similarly noted by Zeng et al (2015) in their 18S rDNA phylogenetic analysis.…”
mentioning
confidence: 63%
“…The work conducted by Chen et al (2011) and by us indicates that the populations of H. strictathecatus used in these studies are very close morphologically and molecularly to a putative Taiwanese population of H. mangiferae (Chen et al, 2011) (Figs 21,J;41,J;12;13) This species was originally described from Myrica cerifera L. from Alturas, FL, USA. It has since been reported from various habitats and localities in Florida, Georgia, Alabama and South and North Carolina (Chitwood & Birchfield, 1957;Dasgupta el al., 1969;Ye & Robbins, 2000;Zeng et al, 2012). Two populations from Florida and one from California were characterised morphologi cally and molecularly in our study.…”
Section: Remarksmentioning
confidence: 93%
“…In this selection of studied sheathoid ne matodes, H. w essoni is the only species having economic relevance because this nematode parasitises and damages many sod grasses, including Bermuda grass (Cynodon dactylon), seashore paspalum (Paspalum vaginatum ), St Augustine grass (Stenotaphrum secundatum ), and Zoysia sp. in Florida and North and South Carolina (Zeng et al, 2012;Crow, 2013).…”
mentioning
confidence: 99%
“…The "bluntly rounded almost truncate tail" as described and illustrated by Raski (1952) is similar in form to many of the Mesocriconema specimens collected in this study. We suspect that nematodes identified as "short-stylet" forms of M. xenoplax from bentgrass in South and North Carolina reported by Zeng et al (2012) and those associated with Bermuda grass and river cane in Arkansas (Cordero et al 2012) may be members of either haplotype group 1 or 15. Only two specimens, a juvenile and adult female from New Mexico, were included in Group 16.…”
Section: Haplotype Groups Groups 1 15 and 16mentioning
confidence: 94%
“…Geraert (2010) also reported that young juveniles have irregular annuli margins, but the larger juveniles have smooth margins. Recent published assessments of M. curvatum diagnostic characters have emphasized that M. curvatum lacks an elevated labial disc, and the labial plates are described as "minute or obvious" (Cordero et al 2012) or irregular (Zeng et al 2012). The full range of morphological variability is evident within the COI haplotype groups that conform and generally key to M. curvatum in Geraert (2010) or Brzeski et al (2002b).…”
Section: Haplotype Groups Groups 1 15 and 16mentioning
confidence: 99%